Objective C: Object event communication methods analysis - Víquez-Acuña, Óscar (2014)
This article shows a series of programming patterns used in event communication in Objective C. Each one of these patterns is explained according to its functionality, a concise example of its day to day use is given and, optionally, a listing of its advantages and disadvantages regarding its own features is presented. In the beginning, some object oriented programming concepts are retaken, so that we don’t lose sight of the topic we’re dealing with. Starting with some of the object orientation pillars, we remember what we seek to have in a greater or minor extent in the software for it to be considered of good quality. Then the model view controller pattern is analyzed, which has been very popular in the last years, and which allows to apply, as it will be shown later, the other event communication patterns. Mentioned patterns are: delegates, notifications, observation and completion blocks. Each one of these communication methods have its own pros and cons. Throughout this article their everyday uses will be discussed. The objective of this analysis is to offer any developer a discussion point when selecting one of these methods for a specific task.